Urchin and the rage tide - McAllister, Margaret (Margaret I.) (McAllister, Margaret (Margaret I.). Mistmantle chronicles, 2010)
After many years of peace and prosperity on the island of Mistmantle, tidal waves suddenly threaten and Urchin of Riding Stars must help the endangered citizens to safety, while he also tries to stop the reckless squirrel Mossberry's rise to power.